Retroviral vector integration occurs in preferred genomic targets of human bone marrow-repopulating cells - Maier-Laufs, Stephanie; Gentner, Bernhard Rudolf; Nagy, Katalin Zsuzsanna; Jauch, Anna; Benner, Axel; Naundorf, Sonja; Kuehlcke, Klaus; Schiedlmeier, Bernhard; Ho, Anthony Dick; Zeller, W. Jens; Frühauf, Stefan (Blood, 2003)
Increasing use of hematopoietic stem cells for retroviral vector-mediated gene therapy and recent reports on insertional mutagenesis in mice and humans have created intense interest to characterize vector integrations on a genomic level. We studied retrovirally transduced human peripheral blood progenitor cells with bone marrow-repopulating ability in immune-deficient mice. By using a highly sensitive and specific ligation-mediated polymerase chain reaction (PCR) followed by sequencing of vector integration sites, we found a multitude of simultaneously active human stem cell clones 8 weeks after transplantation. Vector integrations occurred with significantly increased frequency into chromosomes 17 and 19 and into specific regions of chromosomes 6, 13, and 16, although most of the chromosomes were targeted. Preferred genomic target sites have previously only been reported for wild-type retroviruses. Our findings reveal for the first time that retroviral vector integration into human marrow-repopulating cells can be nonrandom (P = .000 37).